Formation of Corrosion Resistant Hard Coating of Litao3 by Anodizing in Molten Lino3 - Hu, Likun; Yuan, Sicheng; Xie, Panping; Xu, Dengfeng; Peng, Zhi; Xie, Axi; Zheng, Feng (Innovations in Corrosion and Materials Science (Discontinued), 2019)
Background: Lithium tantalate (LiTaO3) thin film was synthesized and in situ coated on tantalum substrate via anodic oxidation. Methods: The effects of temperature, voltage and time on composition, morphology and hardness of film were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and Vickers hardness, respectively. Results: Our results showed that surface hardness of all coated samples has been increased compared with that of pure tantalum. The value of hardness was found to gradually increase with temperature, voltage and reaction time of the coating process. Selected specimens, after coating, were immersed into 10 wt% NaOH solution at 50oC for 96h to explore their anti-corrosion performance. Immersing results indicated that LiTaO3 coated samples have a smaller mass loss and corrosion rate compared to those of pure Ta substrate. Pure tantalum sample and those coated by LiTaO3 thin film were further examined by electrochemical methods including open-circuit potential (OCP), potentiodynamic polarization curves and electrochemical impedance spectra (EIS). Conclusion: We have found that samples coated with LiTaO3 thin film exhibit higher potentials and lower corrosion current densities than those of pure tantalum substrate, according to the results and analysis of OCP curves and potentiodynamic polarization curves. Upon anodic oxidation, samples display higher polarization resistance with higher resistance to corrosion.
Keywords: anodic oxidation